Effects of drying and storage conditions on the stability of TSH in blood spots - Patrícia Künzle Ribeiro Magalhães; Carlos Henrique Miranda; Fernando Crivelenti Vilar; André Schmidt; Roberta Rodrigues Bittar; Giselle Aparecida Caixe de Carvalho Paixão; Edson Zangiacomi Martinez; Léa Maria Zanini Maciel (Archives of Endocrinology and Metabolism, 2018)
ABSTRACT Objective To evaluate the influence of sample drying and storage temperature on TSH stability in neonatal screening. Subjects and methods Blood samples from 29 adult volunteers as a surrogate for neonatal blood (10 with normal TSH, 9 with overt hypothyroid and 10 with subclinical hypothyroidism) were spotted on filter paper and dried at 22°C or 35°C for 3 hours. The samples were then stored at 22°C, -4°C, or -20°C, and TSH measurements were performed at day 0 (D0), D7, D30, D60, D180, and D360 of storage. Results The drying temperature did not interfere with TSH measurement on D0. TSH values remained stable up to D30 when stored at 22°C and were stable up to D60 when stored in a refrigerator or freezer. Samples stored at 22°C had a greater decrease in TSH values than samples stored in a refrigerator or a freezer. Conclusions Freezer storage is not advantageous compared to storage in the refrigerator. At the end of one year, if confirmation of the initial result is required, a reduction of TSH concentrations should be taken into account.